2021
DOI: 10.3389/fpls.2021.794349
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promotion by Two Volatile Organic Compounds Emitted From the Fungus Cladosporium halotolerans NGPF1

Abstract: Microbial volatiles have beneficial roles in the agricultural ecological system, enhancing plant growth and inducing systemic resistance against plant pathogens without being hazardous to the environment. The interactions of plant and fungal volatiles have been extensively studied, but there is limited research specifically elucidating the effects of distinct volatile organic compounds (VOCs) on plant growth promotion. The current study was conducted to investigate the impact of VOCs from Cladosporium halotole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 88 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Fungal VOCs are a large group of carbon-based chemicals with low molecular weights, low polarities, low boiling points, and high vapor pressure ( Jiang et al, 2021 ). These characteristics provide VOCs with advantages over other secondary metabolites of a microbial nature, and these advantages include the abilities to travel long distances, to mediate interactions between organisms that are not in direct contact and to be perceived at low concentrations ( Yusnawan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal VOCs are a large group of carbon-based chemicals with low molecular weights, low polarities, low boiling points, and high vapor pressure ( Jiang et al, 2021 ). These characteristics provide VOCs with advantages over other secondary metabolites of a microbial nature, and these advantages include the abilities to travel long distances, to mediate interactions between organisms that are not in direct contact and to be perceived at low concentrations ( Yusnawan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was not clear how butanal, 2‐methyl and butanal, 3‐methyl are produced in plants. Several studies suggested that they were produced by fungi to promote plant growth (Jiang et al., 2021) or released during the heating of protein and fat (Bhatti et al., 2014). The higher concentration of pentanal in the Howard and Tulare dark kernels, compared to their respective light kernels, and butanal, 2‐methyl and butanal, 3‐methyl in all the dark kernels, indicated oxidation of lipid and possibly protein as well.…”
Section: Resultsmentioning
confidence: 99%
“…35 In recent years, more and more studies have shown that VOCs produced by beneficial microorganisms can not only inhibit the growth of plant pathogens but also promote plant growth. 36 B. velezensis has a strong rhizosphere colonization ability, and it has been reported to have a strong ability to inhibit pathogens and a broad-spectrum plant growth-promoting activities in multiple studies. 37 In this study, we report for the first time the inhibitory effect of B. velezensis against S. rolfsii.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The volatile organic compounds (VOCs) produced by microorganisms have desirable characteristics such as small molecular weight, low boiling point, low polarity, and lipophilicity, which enable VOCs to spread over long distances at very low concentrations, making them important media for the interaction between microorganisms and plants and animals . In recent years, more and more studies have shown that VOCs produced by beneficial microorganisms can not only inhibit the growth of plant pathogens but also promote plant growth B.…”
Section: Discussionmentioning
confidence: 99%